2021
DOI: 10.3389/fphar.2021.749134
|View full text |Cite
|
Sign up to set email alerts
|

FDX1 can Impact the Prognosis and Mediate the Metabolism of Lung Adenocarcinoma

Abstract: Background: Lung cancer has emerged as one of the most common cancers in recent years. The mitochondrial electron transport chain (ETC) is closely connected with metabolic pathways and inflammatory response. However, the influence of ETC-associated genes on the tumor immune response and the pathogenesis of lung cancer is not clear and needs further exploration.Methods: The RNA-sequencing transcriptome and clinical characteristic data of LUAD were downloaded from the Cancer Genome Atlas (TCGA) database. The LAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
104
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(112 citation statements)
references
References 40 publications
8
104
0
Order By: Relevance
“…The above results are consistent with previous studies which proved that the expression levels of FDX1 in the tumor tissues of ACC, KICH, KIRC, KIRP [11] , LIHC [12] , and LUAD [10] were lower than those in the normal tissues.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The above results are consistent with previous studies which proved that the expression levels of FDX1 in the tumor tissues of ACC, KICH, KIRC, KIRP [11] , LIHC [12] , and LUAD [10] were lower than those in the normal tissues.…”
Section: Discussionsupporting
confidence: 93%
“…FDX1 expression can promote the death of tumor cells [10] . What's more, the pathway that FDX1 induces tumor cell death has been illuminated in the recent research titled "Copper ionophore-induced cell death" published in the journal Science [17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDX1 gene codes for a tiny iron-sulfur protein that transports electrons from NADPH to mitochondrial cytochrome P450 via ferredoxin reductase, which is implicated in the steroid, vitamin D, and bile acid metabolism. FDX1 may affect the prognosis of lung adenocarcinoma by mediating metabolism 21 . Lipoyltransferase 1 (LIPT1) is an enzyme that activates TCA cycle-associated 2-ketoacid dehydrogenases, and its deficiency inhibits the metabolism of the TCA cycle 22 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that genetic polymorphisms in FDX1 are associated with IgA nephropathy in the Han Chinese population ( 10 , 11 ). In addition, recent studies have suggested that the FDX1 gene may play important roles in diseases such as lung adenocarcinoma ( 12 ) and polycystic ovary syndrome (PCOS) ( 13 ).…”
Section: Introductionmentioning
confidence: 99%